The risk analysis of major cryptocurrencies: Value-at-risk and Expected shortfall approaches - Fang, Jun (2022)
Purpose: The aim of this paper is to examine the Value-at-Risk (VaR) and Expected Shortfall (ES) of major selected cryptocurrencies through Historical simulation, parameter simulation, and Monte Carlo simulation, and compare with S&P500 Index. In addition, this paper also aims to provide some solid advice to existing or prospective investors in the cryptocurrency market through empirical results.